The Effect of Direct Instruction and Interactive Instructional Videos on Learning Effectiveness and Efficiency in Mathematics Education - Andreas M. Zendler (JME (Journal of Mathematics Education), 2020)
This study focuses on the empirical examination of learning effectiveness and efficiency concerning two instructional methods: Direct instruction and interactive instructional videos. An SPF-2×2•2 design is used to control the instructional method, lessons, and class context. Learning outcome on probability calculation is assessed about effectiveness (grade) and efficiency (time required). The empirical findings show that learning with interactive instructional videos performs well regarding direct instruction. This is a sig nificant result in the digitization of instructional methods.